Urine creatinine concentration and clinical outcomes in older adults: The Cardiovascular Health Study. Issue 12 (7th August 2021) - Barzilay, Joshua I.; Buzkova, Petra; Shlipak, Michael G.; Lyles, Mary F.; Bansal, Nisha; Garimella, Pranav S.; Ix, Joachim H.; Kizer, Jorge R.; Strotmeyer, Elsa S.; Djousse, Luc; Biggs, Mary L.; Siscovick, David; et al.
Abstract: Purpose: Loss of muscle mass and strength are associated with long‐term adverse health outcomes in older adults. Urine creatinine concentrations (Ucr; mg/dl) are a measure of muscle tissue mass and turnover. This study assessed the associations of a spot Ucr level with muscle mass and with risk of hospitalization, mortality, and diabetes mellitus in older adults. Methods: We examined 3424 participants from the Cardiovascular Health Study who provided spot urine samples in 1996–1997 and who were followed through June 2015. All participants underwent baseline measurement of grip strength. In a sub‐cohort, 1331 participants underwent dual energy X‐ray absorptiometry (DEXA) scans, from which lean muscle mass was derived. Participants were followed for a median of 10 years for hospitalizations and mortality, and 9 years for diabetes mellitus. Results: In linear regression analysis, a one standard deviation higher Ucr concentration (64.6 mg/dl) was associated with greater grip strength (kg force) β = 0.44 [0.16, 0.72]; p = 0.002) and higher lean muscle mass (kg) ( β = 0.43 [0.08, 0.78]; p = 0.02). In Cox regression analyses, each standard deviation greater Ucr concentration was associated with lower rates of hospitalizations (0.94 [95% confidence interval, 0.90, 0.98]; p < 0.001) and lower mortality risk (0.92 [0.88, 0.97]; p < 0.001), while a one standard deviation increase in muscle mass derived from DEXA had no such significant association. Ucr levels were not associated with incident diabetes mellitus risk (0.97 [0.85, 1.11]; p = 0.65). Conclusion: A higher spot Ucr concentration was favorably associated with muscle mass and strength and with health outcomes in older community‐living adults. The ease of obtaining a spot Ucr makes it an attractive analyte to use for gauging the health of older adults.